Funding the Green Transition: Governance Quality, Public Debt, and Renewable Energy Consumption in Sub-Saharan Africa - Favour Chidinma Onuoha; Stephen Kelechi Dimnwobi; Kingsley Ikechukwu Okere; Chukwunonso Ekesiobi (African Governance and Development Institute (AGDI), 2023)
Prompted by the renewable energy funding challenge in sub-Saharan Africa (SSA) amid surging public debt in the region, this study investigates the moderating role of governance quality in the relationship between public debt and REC in the region using the Feasible Generalized Least Squares. The study established that public debt positively impacts REC, but the interactive effect of governance quality and public debt impedes REC. Policy prescriptions are put forward to address the funding challenges of transitioning to a green energy future in SSA by highlighting the critical role of governance.
Keywords: 330; Public Debt; Renewable Energy Consumption; Governance Quality; Sub-Saharan Africa